Role of Sodium Bicarbonate to Treat Neonatal Metabolic Acidosis: Beneficial or Not - Afrin, Manifa (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Despite the lack of evidence for effectiveness of sodium bicarbonate in treatment of metabolic acidosis in critically ill patients who are admitted in neonatal and pediatric intensive care unit, bicarbonate administration is a common practice and has a long history of widespread use. The justification for persistent use of this controversial therapy comes from a variety of sources, many of them based in philosophy than in science. Clinicians must consider the intervention which will meet the therapeutic objective & existence of strong scientific evidence. To the contrary, there is increasing evidence of this detrimental therapy and adverse effects include diminished oxygen delivery to tissues, worsening intracellular acidosis, aggravated myocardial injury, fluctuations in cerebral blood flow, intracranial hemorrhage and reduces the likelihood success of resuscitation. This review summarizes the evidence and examines the controversy over the use of bicarbonate to treat metabolic acidosis in neonate. J Bangladesh Coll Phys Surg 2017; 35(2): 80-85